2016
DOI: 10.1074/jbc.r115.686493
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Functions of Vinculin Interactions with Phospholipids at Cell Adhesion Sites

Abstract: The cytoskeletal protein vinculin is a major regulator of cell adhesion and attaches to the cell surface by binding to specific phospholipids. Structural, biochemical, and biological studies provided much insight into how vinculin binds to membranes, what components it recognizes, and how lipid binding is regulated. Here we discuss the roles and mechanisms of phospholipids in regulating the structure and function of vinculin and of its muscle-specific metavinculin splice variant. A full appreciation of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 77 publications
1
52
0
Order By: Relevance
“…No significant difference of expression and distribution of both SCN5A and VCL were observed between the controls and SUNDS cases. As previously reported, 25 we identified that VCL directly interacts with SCN5A in vivo and in vitro using coimmunoprecipitations ( Figure 3A and 3B). Furthermore, VCL-D841H does not affect this physical association between VCL and SCN5A ( Figure 3C and 3D).…”
Section: The Morphological Examination and Immunoprecipitationssupporting
confidence: 87%
See 2 more Smart Citations
“…No significant difference of expression and distribution of both SCN5A and VCL were observed between the controls and SUNDS cases. As previously reported, 25 we identified that VCL directly interacts with SCN5A in vivo and in vitro using coimmunoprecipitations ( Figure 3A and 3B). Furthermore, VCL-D841H does not affect this physical association between VCL and SCN5A ( Figure 3C and 3D).…”
Section: The Morphological Examination and Immunoprecipitationssupporting
confidence: 87%
“…However, using the strict ACMG guideline‐based definition for pathogenicity, D841H was considered as a variant of uncertain significance. D841H localized to the proline‐rich zone (amino acids 837–878), which links the head domain (residues 1–836, harbors binding sites of talin, α‐actin, or α‐catenin) to tail domain (residues 879–1066, harbors paxillin‐binding site) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This domain-swapped intermolecular interaction is strengthened by a tryptophan from one meta/vinculin molecule stacking onto a histidine from another meta/vinculin subunit. Significantly, R975 residing on α-helix H1′ in MV that binds to PIP 2 is replaced by an aspartate in vinculin that is not involved in PIP 2 binding to Vt and is the only amino acid that is not conserved in all combined, MVt or Vt, lipid binding residues in the crystal structures (46). Importantly, the DCM/HCM-associated mutant R975W binds PIP 2 but does not dimerize.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms, binding partners, and modifications have been reported to sever the vinculin head-tail interaction and activate vinculin (46,51). Lipids were originally thought to be involved in activating vinculin (34,36) but inactive vinculin does not bind to PIP 2 (38).…”
Section: Discussionmentioning
confidence: 99%